Learning experiences and college access of American workers: Evidence from PIAAC - Chang Sung Jang; Junghwan Kim; In Tak Kwon (Adult Education Research Conference, 2020)
Using the U.S. data from the Program for the International Assessment of Adult Competencies (PIAAC), this study aims to explore how work-related learning experiences of working adults influence their sub-baccalaureate or baccalaureate degree-seeking in higher education institutions (HEIs). Given many jobs in the U.S. that require higher education credentials, we examined how formal and informal work-related learning experiences are associated with the college access of working adults who have a high school diploma. The multinomial logistic regression results show that work flexibility, distance learning, and private learning experience are positively related to working adults’ college access. Based on the findings, implications for policy and practice were discussed on how industry and organizations could support working adults’ learning opportunities in the workplace and HEIs.
Keywords: formal/informal learning; college access; working adults; PIAAC